2020
DOI: 10.3389/fpls.2020.00586
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Kernel Set and Potential Kernel Weight by Nitrogen Supply and Carbohydrate Availability in Maize Genotypes Contrasting in Nitrogen Use Efficiency

Abstract: Paponov et al. Kernel Number and Weight Formation weight was independent of carbohydrate availability but was related to the N flux per kernel in both genotypes. In conclusion, kernel set and potential kernel weight are regulated independently, suggesting the possibility of simultaneously increasing both sink components in maize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Many studies have discussed that under scarce sucrose conditions, apical kernels are more likely to abort, as they have the weakest sink (Shen et al, 2018 ). Kernel abortion can be minimized by adequate supplies of N, organic, and inorganic substances, and improving carbohydrate availability during the pollination stage (Paponov et al, 2020 ). At high PD, many kernels may not develop an event that occurs in some hybrids following poor pollination resulting from a silking period that is delayed relative to tassel emergence (Otegui, 1997 ) and/or owing to a limitation in assimilate supply that causes the grain and cob abortion in maize (1985).…”
Section: Role Of Stem Sugars In Lodging Resistance and Kernel Abortionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have discussed that under scarce sucrose conditions, apical kernels are more likely to abort, as they have the weakest sink (Shen et al, 2018 ). Kernel abortion can be minimized by adequate supplies of N, organic, and inorganic substances, and improving carbohydrate availability during the pollination stage (Paponov et al, 2020 ). At high PD, many kernels may not develop an event that occurs in some hybrids following poor pollination resulting from a silking period that is delayed relative to tassel emergence (Otegui, 1997 ) and/or owing to a limitation in assimilate supply that causes the grain and cob abortion in maize (1985).…”
Section: Role Of Stem Sugars In Lodging Resistance and Kernel Abortionmentioning
confidence: 99%
“…Nitrogen deficiency may cause kernel abortion, resulting in infertility (Marahatta, 2020 ). Plants grown under high N levels and high PD have decreased kernel numbers because the floret set is established before silking (Gonzalez et al, 2019 ; Mueller et al, 2019 ; Paponov et al, 2020 ). Thus, an adequate supply of N during the lag phase of the grain-filling stage may reduce kernel abortion (Below et al, 2000 ; Mueller et al, 2019 ; Paponov et al, 2020 ).…”
Section: Management Of Stem Lodging and Kernel Abortion In Maizementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Setter and Parra (2010) reported that kernel set was not associated with several sugar fractions (such as glucose and sucrose) and starch concentrations during stress or recovery in the bulk tissues of the pedicel-placenta, pericarp or endosperm of maize. Paponov et al (2020) found a negative correlation between kernel set and sucrose/total sugar ratios in the kernels of maize. They suggested that the potential kernel weight was independent of carbohydrate availability in maize.…”
Section: Carbohydrate Composition Of Yield-based Waxy Corn Groupsmentioning
confidence: 90%
“…As a result, the pre-silking DM accumulation for SD1 and the post-silking DM accumulation for SD3 averagely increased by 17.9 and 8.4% compared to SD2, respectively. Greater pre-silking DM accumulation of maize had an effect on developing kernels, with greater translocation of DM to help establish viable embryos ( He et al, 2005 ; Yan et al, 2017 ; Yu et al, 2021 ), while greater post-silking DM accumulation improved the capacity of maize to provide assimilates during grain filling ( Echarte et al, 2008 ; Ning et al, 2013 ; Paponov et al, 2020 ). Moreover, optimal temperature condition could increase the activities of key enzymes in carbon metabolism of grain, and promote the transport, transformation, and accumulation of assimilates into grains ( Suwa et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%